Analysis Style Member Recruitment by Indonesian Political Parties as Part of Efforts for the Indonesian Parliament Member’s Candidacy - Welasari, Welasari (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study focuses on party member recruitment. The study aims to enable political parties to nurture their members as potential legislator candidates successfully. This research is essential to assist political parties in implementing an ideal recruitment process. This study adopted a literature review as a research method, focusing on the problem of recruitment of political party member recruitment. Parties previously won the elections, namely PDIP, Demokrat, and PKB, are the research subjects. The data was collected through a literature review. The collected data were then analyzed using a literature review approach by examining, identifying, and examining problems by the title. Such data consisted of the three parties' recruitment processes, namely PDIP, Demokrat, and PKB. Patterns of organizational structure and levels in party member development are part of the information obtained in this research. Based on the analysis results, there are several types of styles the recruitment members political parties have used a closed recruitment pattern. Closed recruitment patterns are very thick with forms of deviation, high political dowries, the rise of political transactions and money politics, as well as other forms of irregularities that are not profitable for the party, and using open recruitment style with stages registration, selection, tes administration, filtering, and assignment.